On the importance of central banks watchers: The SNB and its Watchers Conference - Otmar Issing (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2023)
In his speech at the conference "The SNB and its Watchers", Otmar Issing, member of the ECB Governing Council from its start in 1998 until 2006, takes a look back at more than twenty years of the conference series "The ECB and Its Watchers". In June 1999, Issing established this format together with Axel Weber, then Director of the Center for Financial Studies, to discuss the monetary policy strategy of the newly founded central bank with a broad circle of participants, that is academics, bank economists and members of the media on a "neutral ground". At the annual conference, the ECB and its representatives would play an active role and engage in a lively exchange of view with the other participants. Over the years, Volker Wieland took over as organizer of the conference series, which also was adopted by other central banks. In his contribution at the second conference "The SNB and its Watchers", Issing summarizes the experience gained from over twenty years of the ECB Watchers Conference.
Keywords: 330